Dissolution Behaviours of Acetaminophen and Ibuprofen Tablet Influenced By L–HPC 21, 22, and Sodium Starch Glycolate as Disintegrant - Yoga Windhu Wardhana; Dradjad Priambodo (Universitas Padjadjaran (Unpad), 2019)
The dissolution of tablets is one of a drug absorption determinant. Disintegrant agent has play an important role on determining the dissolution of tablets. In this experiment, the dissolution behaviours of Acetaminophen and Ibuprofen Tablet was studied using various disintegrant agent such as Low substituted – Hydroxypropyl Cellulose (L–HPC) 21, L–HPC 22 and Sodium Starch Glycolate (SSG) as comparator. Those disintegrant agents were used at three concentration (6%, 7% and 8%) for every tablets formula. Tablets were made by wet granulation method and pressed using single punch 13 mm flat E. Korsch machine. Evaluation of each tablets quality were conducted include for uniformity of weight and size (diameter and thickness), hardness, friability, disintegration time and dissolution. Physically standards from tablets were in good condition, the standards of the weight and thickness uniformity, hardness and friability met the requirement. The dissolution profile on Acetaminophen Tablets showed that only tablet with 6 % L–HPC 21 did not meet the requirement of FI V (Q = 80%, 30 minutes), but on Ibuprofen Tablets where met the requirement of FI V (Q = 80%, 60 minutes) only tablet with 8% L– HPC 21, 7% and 8% SSG. The conclusion of the study was the L–HPC has more disintegrant character at hydrophilic active ingredients. Key words: Acetaminophen Tablet, Ibuprofen Tablet, SSG, L-HPC 21 and 22, Dissolution Profile